2021
DOI: 10.1007/s11440-021-01199-5
|View full text |Cite
|
Sign up to set email alerts
|

Directionally dependent strength and dilatancy behavior of soil–structure interfaces

Abstract: Soil-structure interfaces typically exhibit a shear behavior that is independent of the direction of relative displacement due to symmetry in the solid material's surface profile. This experimental study investigates the interface shear behavior of surfaces with asymmetric profiles inspired by the scales of snake skin. The results of shear box interface tests on two sandy soils indicate that the peak and residual interface shear strengths and dilatancy are greater when the soil is displaced against the sharp e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Indeed, the changing trend of interface friction angle is affected by the starting shear direction while the shearing sequence has no effect on the interface friction angle. Previous studies 16,21 revealed that volumetric contraction at the trailing end of the scale during the starting shearing densified soil around the scale, difference in the interface friction angle between the cranial and caudal shearing directions was pronounced depending on the starting shearing direction, and thus the caudal first-caudal second shearing sequence produces larger friction difference than the cranial first-cranial second shearing sequence. However, the current study observes that the interface friction angle in the first shearing cycle is almost identical to that in the second shearing cycle, and thus densification effect during the first shearing is diminished.…”
Section: Evolution Of Interface Friction Anglementioning
confidence: 92%
See 2 more Smart Citations
“…Indeed, the changing trend of interface friction angle is affected by the starting shear direction while the shearing sequence has no effect on the interface friction angle. Previous studies 16,21 revealed that volumetric contraction at the trailing end of the scale during the starting shearing densified soil around the scale, difference in the interface friction angle between the cranial and caudal shearing directions was pronounced depending on the starting shearing direction, and thus the caudal first-caudal second shearing sequence produces larger friction difference than the cranial first-cranial second shearing sequence. However, the current study observes that the interface friction angle in the first shearing cycle is almost identical to that in the second shearing cycle, and thus densification effect during the first shearing is diminished.…”
Section: Evolution Of Interface Friction Anglementioning
confidence: 92%
“…Inspired by the frictional characteristics of snakeskin, many studies have replicated the ventral scale geometry to achieve the desired frictional resistance during soil-structure interactions in various geotechnical engineering applications 5,[13][14][15][16][17][18] . The frictional anisotropy induced by the bio-inspired surfaces was qualitatively analyzed using a conventional direct shear apparatus under a single vertical stress of 75 kPa 5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation